Efficiency of charcoal production in Sub-Saharan Africa: Solutions beyond the kiln - (:unkn) unknown (My University, 2019)
With charcoal set to remain an important energy source throughout Sub-Saharan Africa (SSA) in the foreseeable future, this paper focuses on improving the efficiency of carbonisation as one contribution to more sustainable charcoal value chains. While the efficiency of wood-to-charcoal conversion is often considered a technical matter of kiln performance, this study aims to shed light on the role of the enabling institutional context and the capacities of the players involved. We first review initiatives for enhanced charcoal production in different SSA countries. We then compare the data on carbonisation processes in two production areas in the Democratic Republic of Congo: Yangambi and the Bateke Plateau. The main findings are: 1) Large gains in wood-to-charcoal conversion rates are possible by improving carbonisation techniques, but success largely depends on the context-specific appropriateness of kiln solutions, on the capacity and awareness of producers and on the enabling institutional context. 2) Enhancing capacity among operators and other stakeholders requires efficient kiln techniques, but also raising awareness on benefits and sustainable sourcing options, building financial and management skills among producer organisations and improving transportation, handling and marketing. 3) The illegal or informal status of charcoal producers across SSA detracts from the efficiency of charcoal production processes, while an enabling institutional framework facilitates producers' access to permits and funding, provides for simple taxation with incentives for more sustainable practices and links technical requirements for carbonisation to sustainable sourcing and end-uses. The success or failure of improved kiln techniques and related socio-ecological outcomes is co-determined by solutions that include the aspects of capacity enhancement, acceptability and enabling institutions identified in this paper. Further development of these solutions in partners
Keywords: African Research